Efficiency of extinguishing with the water mist system on the example of polyurethane foam fire - Kraus-Namroży, Natalia; Brzezińska, Dorota (Instal, 2020)
Around us, more and more objects are made of polymeric materials. Their properties increase the comfort of everyday life. Unfortunately, due to their structure, they are great fuels. This article presents the structure of polyurethane foams with a description of extinguishing them. The article describes two tests carried out, consisting in extinguishing polyurethane foam samples with a spiral water mist nozzle and the traditional sprinkler. The article also contains a description of research carried out by other researchers and conclusions from the own research.